PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SEKOLAH DASAR - Dwi Mardalena (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the results of student learning science VI low grade of primary school 9 DuriBarat with an average value of 67.14. Therefore, the researchers provide learning alternatives to the applicationby implementing role playing model in class VI SD Negeri 9 Duri Barat. This research aims to improve studentlearning outcomes VI Elementary School science class 9 Duri Barat Application by implementing role playingmodel. This research is a form of classroom action research (PTK) with 2 cycles. Based on research data anlisisafter applying by implementing role playing model, the average percentage of the activity of teachers in the firstcycle of 62.5% increased to 85.25% in the second cycle. The average percentage of student activity alsoincreased 50% in the first cycle increased to 83.3% in the second cycle. Student learning outcomes in basicscore with an average of 67.14 with 50% completion percentage of classes and the first cycle increased with anaverage value of 75.17 class with an increasing percentage of learning outcomes of 11.96% and the percentageof students who complete 57, 14%. Then the average value silus class II increased to 87.85 with the percentageincrease learning outcomes by 30.84% and the percentage of students who completed was 85.71%, after theimplementation by implementing role playing model. These results indicate that the implementation byimplementing role playing model can improve student learning outcomes Elementary School science class VI SDNegeri 9 Duri Barat.